Forecasting Sales Prices Appartment Using Fuzzy Tsukamoto (case Study My Tower Apartment) - Ayu Purnamasari; Wiwiet Herulambang; R Dimas Adityo (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
Currently apartment buildings are not foreign anymore we see let alone in the middle of the city. The price is still fairly cheap or under the price of housing makes a lot of interest to have an apartment either for personal or investment. Each developer has a strategy to attract buyers whether it increases or decreases the price of the apartment in each period or every year. The research was conducted to help the company change the price of the apartment by using method Fuzzy Tsukamoto based on input-an Inflation Value in the year to be predicted, View apartment, and Sales Price before. The results here show that for the output of the program is different from the original data, that is more expensive or the price is higher than the original data. There is an ratio of error 0.7609184% to -0.334665% or difference between Rp.200.000.000 to Rp.400,000.